The impact of brief intensive trauma-focused treatment for PTSD on symptoms of borderline personality disorder. Issue 1 (31st December 2020) - De Jongh, A.; Groenland, G. N.; Sanches, S.; Bongaerts, H.; Voorendonk, E. M.; Van Minnen, A.
ABSTRACT: Background : It is generally recommended to exercise caution in applying trauma-focused treatment to individuals with posttraumatic stress disorder (PTSD) and comorbid borderline personality disorder (BPD). Objective : To investigate the effects of a brief, intensive, direct trauma-focused treatment programme for individuals with PTSD on BPD symptom severity. Methods : Individuals ( n = 72) with severe PTSD (87.5% had one or more comorbidities; 52.8% fulfilled the criteria for the dissociative subtype of PTSD) due to multiple traumas (e.g. 90.3% sexual abuse) participated in an intensive eight-day trauma-focused treatment programme consisting of eye movement desensitization and reprocessing (EMDR) and prolonged exposure (PE) therapy, physical activity, and psychoeducation. Treatment did not include any form of stabilization (e.g. emotion regulation training) prior to trauma-focused therapy. Assessments took place at pre- and post-treatment (Borderline Symptom List, BSL-23; PTSD symptom severity, Clinician Administered PTSD Scale for DSM-5, CAPS-5), and across the eight treatment days (PTSD Checklist, PCL-5). Results : Treatment resulted in significant decreases of BPD symptoms (Cohen's d = 0.70). Of the 35 patients with a positive screen for BPD at pre-treatment, 32.7% lost their positive screen at post-treatment. No adverse events nor dropouts occurred during the study time frame, and none of the patients experienced symptom deterioration in response to treatment. Conclusion : The results suggest that an intensive trauma-focused treatment is a feasible and safe treatment for PTSD patients with clinically elevated symptoms of BPD, and that BPD symptoms decrease along with the PTSD symptoms.